2017
DOI: 10.1177/1753425917699864
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter air pollution from the city of Quito, Ecuador, activates inflammatory signaling pathways in vitro

Abstract: Automobile traffic, industrial processes and natural phenomena cause notable air pollution, including gaseous and particulate contaminants, in urban centers. Exposure to particulate matter (PM) air pollution affects human health, and has been linked to respiratory, cardiovascular and neurological diseases. The mechanisms underlying inflammation in these diverse diseases, and to what extent health effects are different for PM obtained from different sources or locations, are still unclear. This study investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 70 publications
0
22
0
2
Order By: Relevance
“…Nevertheless, to date, only the largest Ecuadorian cities (i.e., Quito, Guayaquil and Cuenca) have established permanent air quality monitoring stations. This follows a general trend throughout Ecuador, where only few studies have reported any effects of fine particulate matter or low air quality [13][14][15].…”
Section: Introductionmentioning
confidence: 81%
“…Nevertheless, to date, only the largest Ecuadorian cities (i.e., Quito, Guayaquil and Cuenca) have established permanent air quality monitoring stations. This follows a general trend throughout Ecuador, where only few studies have reported any effects of fine particulate matter or low air quality [13][14][15].…”
Section: Introductionmentioning
confidence: 81%
“…Despite lots of work done, the mechanism that PM 2.5 aggravated CVDs was still not completely clear. More and more studies suggested that PM 2.5 may be an effective activator of the NLRP3 inflammasome in certain organs . A latest report showed that Al, Cr, Co, Ni, Se, Cd, Ba, Ti, and Pb in PM 2.5 could deposit in the prefrontal cortex of rats and regulate inflammation through NLRP3 inflammasome signal pathway .…”
Section: Discussionmentioning
confidence: 99%
“…More and more studies suggested that PM 2.5 may be an effective activator of the NLRP3 inflammasome in certain organs. 11,28,29 A latest report showed that Al, Cr, Co, Ni, Se, Cd, Ba, Ti, and Pb in PM 2.5 could deposit in the prefrontal cortex of rats and regulate inflammation through NLRP3 inflammasome signal pathway. 30 But in heart, only a report confirmed that IL-1β protein, the key downstream factor of NLRP3 inflammasome activation, played an important role in PM 2.5 -induced cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…38 The inflammasome. 41,42 Activation of NLRP3 results in further production of IL-1β, with consequent downstream effects driving the inflammatory process by signaling the production of IL-6 and hs-CRP. 39 The inflammatory cascade provoked by PM 2.5 is similar to the one instigated in metabolically unhealthy obese patients, in whom metabolically unhealthy adipose tissue is characterized by increased NLRP3 inflammasome activation.…”
Section: Residual CV Risk and Subclinical Inflammationmentioning
confidence: 99%